Imaging sigma receptors in the brain: New opportunities for diagnosis of Alzheimer's disease and therapeutic development. (19th January 2019) - Jia, Hongmei; Zhang, Ying; Huang, Yiyun
Highlights: Neuroimaging of σ receptors in the brain will shed new light on AD pathophysiology. It provides tools for efficacy monitoring of novel AD therapeutic strategies. Neuroimaging of σ1 and σ2 receptors may provide new biomarkers for AD diagnosis. Abstract: The sigma-1 (σ1 ) receptor is a chaperone protein located on the mitochondria-associated membrane of the endoplasmic reticulum, while the sigma-2 receptor (σ2 ) is an endoplasmic reticulum-resident membrane protein. Recent evidence indicates that both of these receptors figure prominently in the pathophysiology of Alzheimer's disease (AD) and thus are targets for the development of novel, disease-modifying therapeutic strategies. Radioligand-based molecular imaging technique such as positron emission tomography (PET) imaging is a powerful tool for the investigation of protein target expression and function in living subjects. In this review, we survey the development of PET radioligands for the σ1 or σ2 receptors and assess their potential for human imaging applications. The availability of PET imaging with σ1 or σ2 receptor-specific radioligands in humans will allow the investigation of these receptors in vivo and lead to further understanding of their respective roles in AD pathogenesis and progression. Moreover, PET imaging can be used in target occupancy studies to assess target engagement and correlate receptor occupancy and therapeutic response of σ1 receptor agonists and σ2 receptor antagonists currently in clinical trials. It is expected that neuroimaging of σ1 and σ2 receptors in the brain will shed new light on AD pathophysiology and may provide us with new biomarkers for diagnosis of AD and efficacy monitoring of emerging AD therapeutic strategies.